A low dielectric polymer with high thermostability derived from bio-based isoeugenol. (5th October 2022) - Zhang, Heng; Sun, Jing; Fang, Qiang
Graphical abstract: Functionalization of biomass isoeugenol gives a fluorine-containing monomer, which is thermally polymerized to obtain a polymer that exhibits a dielectric constant ( D k ) of 2.60 and a dielectric loss ( D f )of 1.40 × 10 −3 at 10 GHz. Highlights: Thermally curing a isoeugenol-based monomer to give a polymer with low D k of 2.60 and D f of 1.40 × 10 −3 at 10 GHz. The polymer displays high thermostability with a T 5d of 483 °C and a char yield of 64% at 1000 °C. This polymer also exhibits good hydrophobicity with a water uptake value of 0.26%. Abstract: A fluorine-containing monomer derived from bio-based isoeugenol has been successfully synthesized. This monomer was thermally cross-linked to form a polymer, displaying good dielectric properties with a dielectric constant ( D k ) of 2.60 and a dissipation factor ( D f ) of 1.40 × 10 −3 at a high frequency of 10 GHz. The polymer also exhibited high thermostability with a weight loss temperature ( T 5d ) of 483 °C, a char yield of 64 % at 1000 °C in N2, a glass transition temperature ( T g ) of 334 °C and a coefficient of thermal expansion (CTE) of 53 ppm/°C at the range of temperatures from 35 to 300 °C. These good comprehensive properties imply that the isoeugenol-based monomer is an ideal precursor for the fabrication of the dielectric materials used in the field of high-frequency communication.